Wave propagation in a hygrothermoelastic half-space along with non-local variable - Vikas Sharma; Praveen Ailawalia; Sunit Kumar (Journal of Applied Science and Engineering, 2024)
This particular work is an effort to investigate the propagation of wave in hygrothermoelastic medium in the light of Eringen’s nonlocal theory of elasticity. The coupled wave equations in terms of displacement, temperature and moisture concentration are solved in an analytical way. The phase velocities of longitudinal displacement wave, transverse displacement wave, diffusion wave and thermal wave, under the influence of nonlocal variable, moisture concentration, and diffusion coefficient, in the medium are obtained analytically and presented graphically to show the effect of these parameters on the wave velocities.